1984
DOI: 10.1007/bf02636251
|View full text |Cite
|
Sign up to set email alerts
|

High pressure splitting of castor oil

Abstract: The effects of variations in pressure (20-40 kg/em2), oil-to-water ratio (1:0.4-1:1, w/w) and time (0-8 hr) on the extent of hydrolysis of castor oil were studied. Higher pressure , lower oil-to-water ratio and longer duration gave higher percentage splits. At 40 kg/em ~ pressure and an oil-to-water ratio of 1:1, ca. 92% split was obtained in 8 hr. When the oil was hydrolyzed in 2 stages at 20 kg/cm ~ with an oil-to-water ratio of 1:0.4, ca. 96% split was obtained in a total period of 10 hr. Splitting at 20 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In case of high temperature steam processes, relatively high temperatures (150°C to 350°C) form the undesired product, ricinoleic acid estolide [6]. It was reported that at 3920 kPa pressure, in a 1:1 oil to water ratio, 92% hydrolysis was obtained in 8 hours; again at 1960 kPa pressure and 1:0.4 oil to water ratio in a 2-stage operation, 96% hydrolysis was achieved in 10 hours [7]. The continuous process employing high pressure (up to 5000 kPa) and temperature (250°C to 360°C), was efficient but ultimately not suitable for denaturation of the product.…”
Section: Fkqolar`qflk=mentioning
confidence: 97%
“…In case of high temperature steam processes, relatively high temperatures (150°C to 350°C) form the undesired product, ricinoleic acid estolide [6]. It was reported that at 3920 kPa pressure, in a 1:1 oil to water ratio, 92% hydrolysis was obtained in 8 hours; again at 1960 kPa pressure and 1:0.4 oil to water ratio in a 2-stage operation, 96% hydrolysis was achieved in 10 hours [7]. The continuous process employing high pressure (up to 5000 kPa) and temperature (250°C to 360°C), was efficient but ultimately not suitable for denaturation of the product.…”
Section: Fkqolar`qflk=mentioning
confidence: 97%
“…A typical pyrolysis reaction is carried out in a tubular batch reactor at 450-600 7C and 1 atm with a residence time of less than 1 min [7,61,77]. The starting material could be either castor oil or methyl ricinoleate [7,61,77,85,86]. The pyrolysis of methyl ricinoleate is the preferred method since castor oil has a higher viscosity, thus resulting in tarry materials and poisonous gases during its direct pyrolysis [7,61,77].…”
Section: Pyrolysis (C7 and C11 Products)mentioning
confidence: 99%
“…Recent studies2 on kinetics of polyamidation of C, dimeric fatty acids, in which both the carboxyl groups are primary, with ethylenediamine showed that the reaction followed overall second-order kinetics with an activation energy of 18.2 kcal/g mol up to 90% conversion and overall third-order kinetics with an activation energy of 16. 4 kcal/g mol above 90% conversion. The present studies pertain to the kinetics of reaction of ethylenediamine with C,, cycloaliphatic dicarboxylic acid, which has one primary and one secondary carboxyl groups, as shown below:…”
Section: Introductionmentioning
confidence: 99%